PEMANFAATAN SENSOR ACCELEROMETER SEBAGAI APLIKASI PEDOMETER BERBASIS ANDROID - Danar Tri Pambudi; Fatsyahrina Fitriastuti; Jemmy Edwin Bororing (Universitas Janabadra, 2018)
Often see people love to workout on holidays. Exercise can prevent many diseases. Some people suffer from overweight because they eat calorie intake is greater than calories expended to conduct the activities, so that the rest of the unused calories they will be stored into fat. The purpose of this research is to design the system by utilizing one of the sensors that are embedded on the android-based smartphone. To produce android-based applications a pedometer that can display information on the mileage, number of steps distance, speed, calories burned. This research utilizes one of the android smartphone namely accelerometer sensor. Accelerometer sensor is essentially one of the features of the sensors that are planted on the Android smartphone that serves to determine the degree of slope of the smartphone using the coordinates of the 3 axis, the axis of X, Y and Z. signal is issued on each sensor is its going to be a FootFall data will be processed to produce an information. Trial results that by utilizing sensors accelerometer pedometer app for android can be made based on android that can be used during sporting activities, especially running and walking. Keywords: Accelerometer Sensor, Android, Foot Step Counters, Mobile Device Applications.